Розробка нейромережевої ітелектуальної системи для прогнозування енергетичних центрівплямових зображень у процесах профілювання лазерного променя - Yarovyy, A. A.; Vlasyuk, R. S. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
The development of a neural net intellectual system for energy centers (EC) spot images forecasting in the processes of laser beam profiling (LB) is done. Actuality of the problem of coordinates forecasting of EC of laser beam profile is proved. Methods of forecasting are considered and the appropriateness of usage the neural net model is justified. Computer simulation of forecasting system is carried out and also on the basis of the obtained results the requirements are formulated and software implementation of intelligent system is performed.